Disclosure of Shariah compliance by Malaysian takaful companies - Abu Kasim, Nor Aziah (Emerald, 2012)
Purpose: This paper seeks to explore the disclosure of Shariah compliance as reported by the Shariah Committee (SC) in the annual reports of takaful companies in Malaysia. Disclosure of Shariah compliance is important in enhancing and protecting the Islamic identity of takaful operators, thereby providing Muslims with an alternative insurance system. The paper also aims to discuss whether the advisory role constrains the SC members to improve disclosure which can boost consumers' confidence and companies' accountability. Both confidence and accountability on Shariah compliance would also help promote Malaysia as an Islamic financial centre. Design/methodology/approach: Content analysis of the SCs' reports in the 2008/2009 annual reports of seven takaful operators in Malaysia were conducted and the findings discussed with three officers from Bank Negara Malaysia (Central Bank of Malaysia). Subsequent to the discussion, the findings were further clarified and confirmed with a former member of the SC through e-mail correspondence. Findings: Disclosure of Shariah compliance by the SC reflects high conformance to the Bank Negara Malaysia guidelines. Although the high level of conformance promotes comparability, it does not necessarily fully address disclosure issues such as providing adequate and relevant information. Shariah compliance by takaful companies seems to develop in much the same manner as other disclosure practices, that is, a tendency to comply with rules rather than with principles. Related to the disclosure issue, SC members are constrained by the advisory role and part-time basis of appointment from fully participating in every stage of product process from its conception to its implementation. Research limitations/implications: The paper relies heavily on Shariah compliance reported by the SC in the annual reports of takaful companies. Nonetheless, findings were confirmed with three officers from Bank Negara Malaysia and with a former member of the SC to enhance the findings' credibility. In future, interviews can be conducted with other stakeholders such as takaful managers, Islamic academics and members of the SC to better understand the nature of disclosure practices by takaful companies. Practical implications: Insights drawn from this study suggest the need to enhance disclosure on Shariah compliance in the SC reports and to further strengthen the role of the SC members. As Shariah governance mechanisms, both the SC reports and SC members can be utilised to enhance the identity of Islamic businesses and fulfils the religious obligations. Originality/value: This paper highlights the need for increased transparency through adequate and relevant disclosure of Shariah compliance information in the SC report of takaful companies. It also raises the concern that the advisory role entrusted to SC members might not be adequate for them to effectively ensure that compliance with Shariah principles are adhered to at all times as expected by Bank Negara Malaysia.